The Influence of Parents' Height and History of Infectious Diseases on Stunting Incidence Children in Wundulako District Kolaka Regency - Ridwan, Muhammad; Sunarsih, Sunarsih; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2023)
Backgrounds: Preliminary surveys that have been conducted in Kolaka Regency show that stunting is caused by various factors, including factors of inadequate nutritional intake for toddlers, inadequate nutritional intake during pregnancy, factors of giving the wrong diet to children, social factors, economics, knowledge and other factors. as well as existing data show that the prevalence of stunting in Kolaka Regency is relatively high. This is the reason for conducting research on the Effect of Parents Height and History of Infection on Stunting Incidents in Children in Wundulako District, Kolaka Regency Methods: Quantitative research uses a cross sectional study design. The population in this study were all children under five aged 0-59 months who were stunted in the working area of ​​the Wundulako Health Center with a total of 218 children under five, the sample was drawn using non-probability sampling with a sample size of 67 under five. Results: Value Statistical Test (X2hit)= 8.242 > X2tab= 3.841, meaning that there is an influence of parents' height and(X2hit)= 36,548 > X2tab =3.841, meaning that there is an effect of a history of infection on the incidence of stunting in Wundulako District, Kolaka Regency. Conclusion: Active efforts are needed to increase information about stunting, and how to prevent it as early as possible, especially for pregnant women who are at risk of giving birth to children with stunting.